(3GdGbJUGO GdfbOjs - (3eMeO(B, (3OhjOGQs ((3GdLRGFQ(B:s (3GdeDSSI GdhWfjI ddafhf GdeWHYjI(B,s, 2004)
(3GdCOGA Gdjhej ddGbJUGO GdQCSeGdj, GdYdGbGJ GdGbJUGOjI GdOhdjI ddEbJUGOjjf, aj GdGbJUGO GdOhdj GdeYGUQ, GdJaSjQ GdfXQj ddYdGbGJ GdGbJUGOjI GdOhdjIs
((3GbJfGAGJ (B2014 1(3f(B)s
Keywords: (3GdEbJUGO GdSjGSjs; (3GdYdGbGJ GdOhdjIs